2018
DOI: 10.21077/ijf.2018.65.2.70567-16
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of fishes of the Bakhira Tal and their conservation status

Abstract: The present study was carried out to assess the ichthyofaunal diversity of Bakhira Tal, a natural wetland in the district Sant Kabir Nagar of Uttar Pradesh. A total of 31 species belonging to 23 genera, 9 orders and 21 families were recorded. Maximum number of species recorded was from the Order Cypriniformes (32.25%), which was followed by Perciformes (25.80%), Siluriformes (16.12%), Ophiocephaliformes (9.67%), Beloniformes (3.22%), Cyprinidontiformes (3.22%), Symbranchiformes (3.22%), Mastacembeleformes (3.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…They also found the family Cyprinidae showed maximum individual diversity. Later, Bano and Seraiuddin [37] recorded 31 species belonging to 23 genera, 9 orders and 16 families were recorded from Bakhira Tal, Uttar Pradesh. Gautam et al [52] reported 24 species of fishes from Rihand reservoir, Uttar Pradesh.…”
Section: Population Structure Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found the family Cyprinidae showed maximum individual diversity. Later, Bano and Seraiuddin [37] recorded 31 species belonging to 23 genera, 9 orders and 16 families were recorded from Bakhira Tal, Uttar Pradesh. Gautam et al [52] reported 24 species of fishes from Rihand reservoir, Uttar Pradesh.…”
Section: Population Structure Studiesmentioning
confidence: 99%
“…Sarwade and Khillare [56] reported 60 species from Ujani wetland where Cyprinidae was dominant with 36 species. Das and Sabitry [57] reported 62 ornamental fish species from the river island, Masuli, Assam where as Cyprinidae was dominant with 10 species reported from Asan wetland, Dehradun by Ishaq and Khan [58] .Kumar et al [19] reported 6 species from Sandi wetland where as Bano and Seraiuddin [37] recorded 10 species from Bakhira Tal, Uttar Pradesh. Das [18] studied the occurrence of 40 species of fishes belonging to 31 genera under six orders and 15 families from Rasik beel wetlands, West Bengal.…”
Section: Population Structure Studiesmentioning
confidence: 99%
See 1 more Smart Citation